33rd AIAA Applied Aerodynamics Conference 2015
DOI: 10.2514/6.2015-3313
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of Passive Load Reduction under dynamic inflow conditions

Abstract: Wind turbines often operate in highly turbulent conditions where the angle of attack can change significantly. The resulting aerodynamic load fluctuations are transmitted from the blades to the drive train and tower. These unsteady loads increase fatigue, which decreases lifetime and limits the upscaling of turbines. State-of-the-art pitch mechanisms are designed to alleviate load fluctuations in the order of minutes to hours but are too slow to account for high frequency fluctuations due to turbulence. Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…11 If a gust passes through such a spatially variable velocity field, its characteristics are altered. 12 All these factors which may cause deviations between theoretical predictions and practical situations are not fully understood. Hence theoretical approaches described above have to be validated experimentally for correct application.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 If a gust passes through such a spatially variable velocity field, its characteristics are altered. 12 All these factors which may cause deviations between theoretical predictions and practical situations are not fully understood. Hence theoretical approaches described above have to be validated experimentally for correct application.…”
mentioning
confidence: 99%
“…Then the sinusoidal shape of the gust is distorted, causing variations in the amplitude of its associated velocity field which is related to the fluctuating pressure through unsteady Bernoulli's equation. 12 Thus there is a significant reduction in the fluctuating pressure difference over the front half of the airfoil, and the variation of the fluctuating pressure on the upper side is more significant, compared to the lower side. It can be observed that the distortion shows a frequency dependence.…”
mentioning
confidence: 99%